Acute Toxicity LD50 Fraction Ethyl Acetate Aquilaria malaccensis, Ficus benjamina, Mikania micrantha, and Fraction Water Cinnamomum burmanii in Mus Musculus - Rizky Yulion; Santi Perawati; Barmi Hartesi; Lia Anggresani; Lili Andriani; Lesra Indriani; Lara Syahila; Suci Ramadani; Nadia Monika (Biology, Medicine, & Natural Product Chemistry, 2023)
Research on the acute toxicity of LD50 had been carried out on the ethyl acetate fraction of Gaharu leaves (Aquilaria malaccensis), beringin leaves (Ficus benjamina), sembung rambat leaves (Mikania micrantha), and kayu manis cortex (Cinnamomum burmanii) water fraction the base of use as traditional treatment by the Suku Anak Dalam (SAD) empirically obtained from ancestors. This research methodwas experimental and it used male and female mice. The control group was given a 1% NaCMC doses of 625 mg/kg body weight, 1,250 mg/kg body weight, 2,500 mg/kg body weight, and 5,000 mg/kg body weight. The test preparation was administered orally once per day. The Thomson-Weil method was used for the measurement of LD50 values. The weight ratio of organs was applied for heart, liver, lungs, kidneys, and stomach. The results showed that the LD50 value for male mice was 2454mg/kg body weight; 2454mg/kg body weight; 1546 mg/kg body weight and 2065mg/kg body weight respectfully. The LD50 value for female mice was a pseudo LD50. The value of the organ weight ratio in each sample showed P<0.05 values that were obtained in gaharu leaves in the liver and kidney organs (male); heart in females. Beringin leaves value P<0.05 lung organs (male). Sembung rambat leaves P<0.05 values of the heart, liver, and stomach organs (male); heart and stomach (female). Cinnamomum cortex value P<0.05 liver and stomach organs (male). The conclusions showed that the LD50 value of the ethyl acetate fraction of gaharu leaf, sembung rambat leaf, beringin leaf, and kayu manis cortex in male mice was slightly toxic, while in female mice it could not be counted.